Reading Don't Fix No Chevys (Yet!): Motivating Boys in the Age of the Common Core. Issue 4 (30th October 2014) - Wilhelm, Jeffrey D.; Smith, Michael W.
Abstract: Research establishes that boys underperform in literacy relative to girls. If boys are to be successful on the assessments designed to measure achievement on the Common Core State Standards (CCSS) and if they are to become lifelong readers, they must be motivated to embrace instruction designed both to prepare them for success and to experience the pleasure and power of reading. Unfortunately, the authors of the standards have been advocating instruction that is radically at odds with what we have learned about what motivates young men. In this commentary we'll review the key findings of our Chevys study, supplementing the work we did there with one of our more recent projects, examine how what we found stacks up against the instructional ideas being proffered by David Coleman and other authors of the CCSS, and suggest alternative approaches to achieving the CCSS that are more in‐line with what we've learned.